The role of tourism media in stimulating desert tourism in Algeria : State of Biskra as a model - Belaghlem, Noureddine; Rais, Hadda (Journal of Human Sciences, 2022)
The research paper aims to highlight the role of the tourism media in revitalizing tourism in Algeria, in order to create and encourage tourism on the one hand, and to promote cultural behaviors in dealing with tourists, tourism facilities and the environment on the other hand, and this study concluded that the contribution of the tourism media in the definition and The promotion of desert tourism in Algeria is a small contribution and does not coincide with the great potential that the Sahara has in Algeria.